Orchid bee baits attracting bees of the genus Megalopta (Hymenoptera, Halictidae) in Bauru region, São Paulo, Brazil: abundance, seasonality, and the importance of odors for dim-light bees - Knoll,Fátima R. N. (2012)
Nocturnal bees in the genus Megalopta Smith, 1853 are generally collected using artificial light sources. However, between 1993 and 2000, a total of 946 females (no males were captured) were captured using aromatic baits commonly used for orchid bees (Euglossini) in five localities in Bauru region, São Paulo, Brazil. Aromatic compounds used in bait traps were: benzyl acetate, eucalyptol, eugenol, skatole, methyl salicylate, and vanillin. The Megalopta species collected were: M. guimaraesi (71.2% of total number of specimens), M. amoena (28.1%), and M. aegis (0.6%). Using the data from these traps, we showed that there was a positive and significant correlation between the abundance of individuals and meteorological factors, rainfall and temperature. Bees were more commonly collected in the spring (September to December) and summer (December to March) than in the autumn and winter, the latter characterized for being a drier and colder period. Variations in the abundance were also detected among localities and years. The most attractive compounds were eugenol (54%), methyl salicylate (22%), and eucalyptol (16%). The ability to detect smells may have an important role in searching for flowers during dim-light conditions. We suggest the use of aromatic compounds in future studies on the biology of Megalopta in the Neotropical region.